Donor Site Aesthetic Enhancement With Preoperative Botulinum Toxin in Forehead Flap Nasal Reconstruction. Issue 5 (November 2016) - Zelken, Jonathan; Yang, Shih-Yi; Chang, Chun-Shin; Chang, Cheng-Jen; Yang, Jui-Yung; Chuang, Shiow-Shuh; Chen, Hung-Chang; Hsiao, Yen-Chang
Abstract : Background: Donor site scarring after forehead flap nasal reconstruction is acceptable. However, as aesthetic outcomes standards for cosmetic and reconstructive surgery merge, we aim to enhance results. We recently demonstrated the cosmetic benefit of botulinum toxin type A (BTX-A) for cleft lip cheiloplasty outcomes. We hypothesize that similar mechanism(s) benefit forehead flap donor scars. Methods: A single surgeon performed 26 forehead flap reconstructions. Indications were cancer ( n = 17), trauma ( n = 3), and congenital deformity ( n = 6). In this split-scar study half the forehead was pretreated with BTX-A and half with normal saline after random assignment. Photographs were evaluated at most recent follow-up. Scar evaluation was based on photographs by 3 plastic surgeons using a composite subjective visual analogue score (VAS). Results: Photographic follow-up was 27 months (range, 10–60 months). Botulinum toxin type A was assigned to the upper forehead in 16 cases and lower forehead in 10 cases. Intrarater reliability among 4 evaluators of 104 VAS scores was 78.1%. Upper forehead VAS (7.9 ± 1.2) was not different than lower forehead VAS (7.9 ± 1.2) regardless of treatment ( P = 0.62). The VAS score of BTX-A–treated scars (8.5 ± 1.0) was significantly higher than the control (7.3 ± 1.1; P < 0.0001). Among 104 individual comparisons (26 patients × 4 observers), there were 73 instances (70.2%) where the experimental VAS score was higher than the control. Conclusions: Preoperative BTX-A injection is feasible and enhances donor site scar appearance after forehead flap nasal reconstruction in an Asian population.